A Comparative Study of Inflammatory Myofibroblastic Tumors and Tumefactive IgG4-related Inflammatory Lesions: the Relevance of IgG4 Plasma Cells. Issue 10 (November 2016) - Chougule, Abhijit; Bal, Amanjit; Das, Ashim; Agarwal, Ritesh; Singh, Navneet; Rao, Katragadda L.N.
Abstract : IgG4-related disease is a recently recognized systemic condition characterized by tumefactive lesions at various sites. Inflammatory pseudotumor (IPT), a tumefactive mass lesion with an unknown etiology, belongs to the spectrum of IgG4-related disease. Inflammatory myofibroblastic tumor (IMT), previously considered under the umbrella of IPT, is now classified as a clonal neoplasm. Previously, both the terms were used interchangeably, because of overlapping morphologic features. This study was carried out to compare the morphologic and the immunohistochemical features of these entities and to study the role of IgG4 in their pathogenesis. Thirty-nine cases comprising of IMT (n=18) and IPT (n=21) were retrieved, and their clinical, morphologic, and immunohistochemical features were studied. IMT was more common in children as compared with IPT. IMT cases showed the proliferation of myofibroblastic cells accompanied by a variable inflammatory infiltrate, whereas IPT cases showed predominantly stromal fibrosis and a lymphoplasmacytic infiltrate with a subset of cases showing a storiform fibrosis and obliterative phlebitis. Anaplastic lymphoma kinase-1 (ALK-1) was positive in 12 of the 18 (66.7%) IMT cases, whereas none of the IPT cases showed ALK-1 immunoreactivity. IPT cases showed significantly increased IgG4+ plasma cells (mean, 127.8/high-power fields vs. 17.8/high-power fields) and a higher IgG4/IgG ratio (mean, 48.2% vs. 10.7%) as compared with IMT. Fluorescence in situ hybridization analysis was positive for ALK rearrangement in 6 of the 9 IMT cases tested. In conclusion, most of the IPT cases can be considered as IgG4 related on the basis of their histopathologic features and immunohistochemistry criteria. However, IMT represents a myofibroblastic neoplasm with ALK-1 overexpression and is clearly not IgG4 related.